Relation of Reproductive and Economic Functions to the Selection of Long-Term Contraception in Women of Fertile Couples in Belukur Makmur Village, Rundeng Sub-District, Subulussalam City - Irma Yuspita Sari Siahaan; Heru Santosa; Sri Rahayu Sanusi (Britain International for Academic Research (BIAR) Publisher, 2020)
One of the population problems faced by the Indonesian people today is a large population and high maternal mortality rates. One way to suppress this growth rate is that the achievement of long-term contraceptive use must reach 65% and the role of family members in motivating the selection of contraceptives is needed. The study aimed to analyze the relationship of reproductive function and family economy with the selection of long-term contraception in women of childbearing age in Belukur Makmur Village, Rundeng Sub-District, Subulussalam Municipality. This type of research is analytical research with a cross sectional approach. The study was conducted in Belukur Makmur Village, Rundeng Sub-District, Subulussalam City, with a sample of 123 people using contraception, data collection was done by interview using a questionnaire. Data were analyzed using the chi square test. The results showed that there was a relationship between reproductive function (p = 0.014) and economic function (p = 0.006) with the selection of long-term contraception in women of childbearing age in Belukur Makmur Village, Rundeng District, Subulussalam City. Recommended to the medical workers to improve education, socialization and motivating couples of childbearing age to choose a long-term contraceptive devices through a family approach.